2010
DOI: 10.1007/s12355-010-0028-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic similarity among genotypes of sugarcane estimated by SSR and coefficient of parentage

Abstract: The aim of this study was to analyze the genetic similarity in commercial cultivars of sugarcane from the breeding program cultivars RB (Republic of Brazil), using SSR markers and coefficient of parentage. Eighteen microsatellite markers were used to estimate genetic similarity in 30 genotypes and coefficient of parentage was estimated in 28 accessions. Eighteen primer pairs produced an average of 3.2 alleles, the level of polymorphism (PIC value) ranged from 0.34 to 0.78 in SMC248CG and SCC2 primers, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
1
11
0
2
Order By: Relevance
“…The number of alleles detected in our study ranged from 2 to 8 per locus, which was similar to what has been reported for other RB sugarcane varieties (Silva et al, 2012) using different SSR primers. The mean number of alleles estimated in our study (4.12 alleles/locus) was also approximately consistent with the mean number of alleles reported in other RB sugarcane varieties (3.2 alleles/locus) (Duarte-Filho et al, 2010), indicating the great potential and high reproducibility of these microsatellite loci to investigate genetic divergence in the sugarcane germplasm. Using a higher number of SSR primers, other breeding programs have reported a correspondingly higher number of alleles at SSR loci (Singh et al, 2008(Singh et al, , 2011Oliveira et al, 2009;Liu et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The number of alleles detected in our study ranged from 2 to 8 per locus, which was similar to what has been reported for other RB sugarcane varieties (Silva et al, 2012) using different SSR primers. The mean number of alleles estimated in our study (4.12 alleles/locus) was also approximately consistent with the mean number of alleles reported in other RB sugarcane varieties (3.2 alleles/locus) (Duarte-Filho et al, 2010), indicating the great potential and high reproducibility of these microsatellite loci to investigate genetic divergence in the sugarcane germplasm. Using a higher number of SSR primers, other breeding programs have reported a correspondingly higher number of alleles at SSR loci (Singh et al, 2008(Singh et al, , 2011Oliveira et al, 2009;Liu et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…While the genetic similarity among the 9 sugarcane varieties ranged from 0.6242 (RB92579 and RB935744) to 0.8631 (RB92579 and RB72457), the genetic similarity that was estimated in 30 accessions of other RB varieties ranged from 0.56 (RB928054 and RB813904) to 0.95 (RB93509 and RB931011) (Duarte-Filho et al, 2010). The Nei identity values obtained for the 9 sugarcane varieties showed a small genetic basis, which was in contrast to the larger genetic basis reported for other sugarcane accessions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In sugarcane, studies evaluating the genetic diversity have been conducted with the use of quantitative and qualitative traits, and/or with molecular markers (Da Silva et al, 2008;Oliveira et al, 2009;Duarte Filho et al, 2010;Dutra Filho et al, 2011;Sindhu et al, 2011;Santos et al, 2012;Santchurn et al, 2012;Perera et al, 2012). In these works, a high degree of genetic similarity between the genotypes has been found, resulting in the formation of few groups.…”
Section: Resultsmentioning
confidence: 99%
“…Although microsatellites have co-dominant inheritance (Tautz, 1989;Weber and May, 1989), the analysis of SSR loci in sugarcane has been especially useful to evaluate genetic distances among sugarcane varieties (Singh et al, 2008(Singh et al, , 2011Oliveira et al, 2009;Duarte-Filho et al, 2010;Liu et al, 2011;Silva et al, 2012). The estimation of genetic diversity within each variety from the mean expected heterozygosity (H E ) is inaccurate since cultivated sugarcane varieties have one of the most complex plant genomes, carrying variable chromosome numbers (Grivet and Arruda, 2002).…”
Section: Introductionmentioning
confidence: 99%